The rich and the poor: environmental biodiversity protecting from allergy. Issue 5 (October 2016) - Ruokolainen, Lasse; Fyhrquist, Nanna; Haahtela, Tari
Abstract : Purpose of review: It has been proposed that biodiversity loss leads to reduced interaction between environmental and human microbiotas. This, in turn, may lead to immune dysfunction and impaired tolerance mechanisms in humans. That is, contact with environmental biodiversity is expected to protect from allergies. However, direct evidence linking contact with biodiversity and risk of allergy has been lacking. In this review, we consider the latest research on the biodiversity hypothesis of allergy. Recent findings: It is becoming clear that what you eat, drink, inhale, and touch all contribute to the grand scheme of host–microbial crosstalk that is needed for a balanced, healthy immune system to develop and maintain a healthy recognition between harmful and harmless invasions. Microbes can either communicate directly with host immune cells or affect the host via metabolism that can even lead to epigenetic modifications. Our living environment plays a key role in this process. Although especially, early exposure to diverse, beneficial microbiota from the environment is repeatedly found crucial, studies on immigrants demonstrate that condition in later life can also be decisive. Conclusion: We are still lacking a more detailed understanding of the interaction between natural, environmental biodiversity, and health, which calls for new innovative and more long-term investigations. The outcomes should be utilized in policy and urban planning efforts, promoting human interaction with natural biodiversity, and supporting a healthy lifestyle.